Strategies for the enhancement of natural resources: Case study canton Bolívar, Manabí-Ecuador (Research, Society and Development, 2025)
The objective of this research was to carry out a territorial analysis of the natural heritage to enhance the natural resources of the Bolívar canton. Therefore, bibliographic studies were proposed, and the exploratory method and a mixed approach were implemented that allowed in-depth knowledge of the topic in question, 8 surveys were also used which were directed at managers of the Decentralized Autonomous Government of the Bolívar canton, an Academic Institution, parish presidents and local actors in the area, the coordinates of natural resources were also surveyed. Among the main findings, the Bolívar canton has a territory that is 80% rural, in which natural resources converge with great relevance for developing tourist activities. By updating the existing natural resource files in the study area, 5 that have great relevance were prioritized. interest. In addition, it was demonstrated that currently, the canton lacks economic support for the valorization of its resources, and sustainable marketing strategies were carried out that value the resources finally a proposal for an action plan was developed detailing strategies that can be considered to enhance the value of natural resources.